Analysis of the Impact of Intercooler Effectiveness Reduction On Combustion Air Pressure and Fuel Consumption OF THE MAIN ENGINE OF THE NINGBO 8300 MV SEMANGAT MAS - Pratama, Faris Dida; Saktiono, Maxima Ari; Dewantara, Belly Yan (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2026)
The decrease in intercooler effectiveness in a ship's main engine can significantly affect performance and fuel efficiency. This final project aims to analyze the impact of the decrease in intercooler effectiveness on combustion air pressure and fuel consumption of the main engine of the Ningbo 8300 MV Semangat Mas. The research was conducted using observation methods and data analysis from measurements obtained during the ship's operation. The collected data includes combustion air pressure, intake air temperature, and fuel consumption under normal engine conditions and conditions with decreased intercooler effectiveness. The results of the study show that the decrease in intercooler effectiveness causes an increase in intake air temperature, which in turn raises combustion air pressure and fuel consumption. This phenomenon indicates that the decrease in intercooler performance can worsen fuel efficiency and reduce overall engine performance. The conclusion of this research highlights the importance of routine intercooler maintenance to ensure the optimal performance of the ship's main engine, reduce fuel consumption, and improve the ship's operational efficiency.